SMAC/Diablo-dependent apoptosis induced by nonsteroidal antiinflammatory drugs (NSAIDs) in colon cancer cells - Kohli, Manu (National Academy of Sciences, 2004)
Nonsteroidal antiinflammatory drugs (NSAIDs) form a paradigm for the chemoprevention of cancer, preventing colonic tumor progression in both experimental animals and humans. However, the mechanisms underlying the antineoplastic effects of NSAIDs are currently unclear. We found that the mitochondrial second mitochondrial-derived activator of caspase (SMAC)/direct inhibitor of apoptosis protein-binding protein with low pI (Diablo) protein translocates into the cytosol during NSAID-induced apoptosis in colon cancer cells. When SMAC/Diablo is disrupted by homologous recombination and RNA interference in these cells, the NSAID-induced apoptosis is abrogated. Biochemical markers of apoptosis, such as caspase activation, cytosolic release of cytochrome c and apoptosis-inducing factor, and mitochondrial membrane potential change, are accordingly decreased. These results establish that SMAC/Diablo is essential for the apoptosis induced by NSAIDs in colon cancer cells.